Mechanistic role of long non-coding RNAs in the pathogenesis of metabolic dysfunction-associated steatotic liver disease and fibrosis - Henry Wade; Kaichao Pan; Bingrui Zhang; Wenhua Zheng; Qiaozhu Su (eGastroenterology)
Metabolic dysfunction-associated steatotic liver disease (MASLD), previously referred to as non-alcoholic fatty liver disease, encompasses a broad range of hepatic metabolic disorders primarily characterised by the disruption of hepatic lipid metabolism, hepatic lipid accumulation and steatosis. Severe cases of MASLD might progress to metabolic dysfunction-associated steatohepatitis, characterised by hepatic inflammation, hepatocyte ballooning degeneration, activation of hepatic stellate cells (HSCs) and fibrogenesis. It may further progress to hepatocellular carcinoma. In the liver, long non-coding RNAs (lncRNAs) target multiple metabolic pathways in hepatocytes, HSCs, and Kupffer cells at different stages of MASLD and liver fibrosis. In this study, we overview recent ﬁndings on the potential role of lncRNAs in the pathogenesis of MASLD and liver fibrosis via modulation of de novo lipid synthesis, fatty acid β-oxidation, lipotoxicity, oxidative stress, metabolic inﬂammation, mammalian target of rapamycin signalling, apoptosis, ubiquitination and ﬁbrogenesis. We critically assess the literature reports that investigate the complex interplay between lncRNA, microRNA and key mediators in liver injury, in both human participants and animal models of MASLD and liver ﬁbrosis. We also highlight the therapeutic potential of lncRNAs in chronic liver diseases.